Effects of short‐term sitagliptin treatment on immune parameters in healthy individuals, a randomized placebo‐controlled study. (8th September 2013) - Price, J. D.; Linder, G.; Li, W. P.; Zimmermann, B.; Rother, K. I.; Malek, R.; Alattar, M.; Tarbell, K. V.
Summary Sitagliptin, a dipeptidyl‐peptidase 4 (DPP‐4) inhibitor, improves blood glucose control in patients with type 2 diabetes by blocking cleavage of glucagon‐like peptide 1 (GLP‐1). In type 2 diabetes patients sitagliptin use is associated with an increase in minor infections, and in new‐onset type 1 diabetes patients the ability of sitagliptin to dampen autoimmunity is currently being tested. DPP‐4, also known as CD26, is expressed on leucocytes and can inactivate many chemokines important for leucocyte migration, as well as act as a co‐stimulatory molecule on T cells. Therefore, this study was conducted to test whether sitagliptin is immunomodulatory. In this randomized, placebo‐controlled trial, healthy volunteers were given sitagliptin or placebo daily for 28 days, and blood was drawn for immune assays. No significant differences were observed in the percentage of leucocyte subsets within peripheral blood mononuclear cells (PBMCs), plasma chemokine/cytokine levels or cytokines released by stimulation of PBMCs with either lipopolysaccharide (LPS) or anti‐CD3. Individuals taking sitagliptin displayed increases in the percentage of cells expressing higher levels of CD26 at early time‐points compared to placebo controls, but these differences resolved by day 28 of treatment. Therefore, in healthy volunteers, treatment with sitagliptin daily for 28 days does not overtly alter systemic immune function.